2020
DOI: 10.1111/febs.15555
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes and signaling pathways for maintenance of quiescence in adult neural stem cells

Abstract: Quiescence is a cellular strategy for maintaining somatic stem cells in a specific niche in a low metabolic state without senescence for a long period of time. During development, neural stem cells (NSCs) actively proliferate and self-renew, and their progeny differentiate into both neurons and glial cells to form mature brain tissues. On the other hand, most NSCs in the adult brain are quiescent and arrested in G0/G1 phase of the cell cycle. Quiescence is essential in order to avoid the precocious exhaustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 93 publications
(138 reference statements)
0
14
0
Order By: Relevance
“…Neurogenesis in the DG of the hippocampus is observed throughout the lifetime of mammals, and the differentiation of NSCs in the hippocampus can be dependent on the tissue environments, including mechanical cues (Urban et al, 2019;Kobayashi and Kageyama, 2021). Indeed, several in vitro studies have shown that mechanical stiffness affects the migration and differentiation of NSCs (see ''Introduction'' section).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurogenesis in the DG of the hippocampus is observed throughout the lifetime of mammals, and the differentiation of NSCs in the hippocampus can be dependent on the tissue environments, including mechanical cues (Urban et al, 2019;Kobayashi and Kageyama, 2021). Indeed, several in vitro studies have shown that mechanical stiffness affects the migration and differentiation of NSCs (see ''Introduction'' section).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported on heterogeneous tissue stiffness in the rodent hippocampus at the neonatal, juvenile, and adult stages (Elkin et al, 2010;Antonovaite et al, 2021). Based on such findings, it is deduced that the stiffness may be related to the niche of NSCs and their activity, including the maintenance and regulation of NSCs (Urban et al, 2019;Kobayashi and Kageyama, 2021). Indeed, it is reported that the mechanical stiffness of the stem cell niche in the SVZ can regulate NSC activity (Kjell et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…NSCs, which are derived from the neuroepithelium of the neural tube, maintain the ability to self-renew and to give rise to neurons, astrocytes, and oligodendrocytes throughout a whole life. Two generally accepted canonical domains in the adult central nervous system that keep a reservoir of NSCs are the subventricular zone near the lateral ventricles and the subgranular zone of the dentate gyrus, where most of the NSCs remains quiescent ( Cheung and Rando, 2013 ; Urban et al, 2019 ; Kobayashi and Kageyama, 2021 ). The quiescent state of NSCs, which is characterized by low metabolic rate and low protein and RNA synthesis, is vital to the preservation of their genomic integrity and essential functional properties ( Cavallucci et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…NSCs, which are derived from the neuroepithelium of the neural tube, maintain the ability to selfrenew and to give rise to neurons, astrocytes, and oligodendrocytes throughout a whole life. Two generally accepted canonical domains in the adult central nervous system that keep a reservoir of NSCs are the subventricular zone near the lateral ventricles and the subgranular zone of the dentate gyrus, where most of the NSCs remains quiescent (Cheung and Rando, 2013;Urban et al, 2019;Kobayashi and Kageyama, 2021). The quiescent state of NSCs, which is characterized by low metabolic rate and low protein and RNA synthesis, is vital to the preservation of their genomic integrity and essential functional properties (Cavallucci et al, 2016).…”
Section: Introductionmentioning
confidence: 99%